A educação como prática da cidadania LGBT no Movimento do Espírito Lilás MEL (1992 2020) - Gomes, José Cleudo (2022)
The present research investigated the educational practice of the Movement of the Lilac Spirit (MEL), founded in 1992 with a focus on confronting prejudice and discrimination of Lesbians, Gays, Bisexuals, Transvestites and Transgendered (LGBT) people in the State of Paraíba. The MEL throughout its trajectory has been developing a community dimension of its educational practice that has provided networking, thus becoming a singular political subject in the proposition of public policies for LGBT people at the national, state, and local levels. The general objective of the study was to analyze MEL's educational and sociopolitical actions in light of education in and for human rights (1992-2020), and to verify to what extent they have contributed to the emancipation and achievement of LGBT citizenship. This main objective gives rise to other more specific ones related to: identify the MEL's historical trajectory and institutional memory as a collective; identify the actions, contents, and methodologies focused on the institution's educational work; investigate the MEL's contributions as an educational space and a social movement struggle space. The research was developed from a dialectical approach, dialoguing with theoretical references from the LGBT movement, popular education, and human rights education. This is a qualitative research of exploratory nature, involving the documental research of the educational materials and socio-political actions produced by the entity, such as the newsletter A Colmeia, besides the semi-structured interviews carried out with ten militants who work or have worked in the social movement, whose reminiscences of memories contributed to identify the actions carried out by MEL. The results of the analyses pointed out that the MEL has an educational practice focused on promoting human rights and LGBT citizenship. Throughout the study, playful, cultural, and socio-political activities were identified that were carried out in an engaged manner in the formative processes of the group that was now forming for LGBT citizenship, since the MEL has a dialectical nature, in which not to separate the cultural, the educational, and the political. Finally, the MEL, as a political grouping was present and active with its militancy, from the struggles for emancipation to the recognition of LGBT citizenship, transforming lives, through its educational and sociopolitical practice that aimed at criticality, autonomy, and the utopia that another country would be possible with rights and public policies for the LGBT population.